2022
DOI: 10.3390/life12101567
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Bone Marrow Mesenchymal Stem Cells Alleviate Ischemia-Reperfusion Injury and Promote Survival of Skin Flaps in Rats

Abstract: Free tissue flap transplantation is a classic and important method for the clinical repair of tissue defects. However, ischemia-reperfusion (IR) injury can affect the success rate of skin flap transplantation. We used a free abdomen flap rat model to explore the protective effects of exosomes derived from bone marrow mesenchymal stem cells (BMSCs-exosomes) against the IR injury of the skin flap. Exosomes were injected through the tail vein and the flaps were observed and obtained on day 7. We observed that BMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The levels of inflammatory cytokines IL-6, TNF-α and IL-1β were measured using ELISA kits as described [ 36 ]. The serum of mice was obtained by centrifugation of 1500 g and 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of inflammatory cytokines IL-6, TNF-α and IL-1β were measured using ELISA kits as described [ 36 ]. The serum of mice was obtained by centrifugation of 1500 g and 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxiainduced exosomes have stronger effects than normal exosomes 12 . In our previous studies, we found that hypoxia-induced exosomes derived from bone marrow mesenchymal stem cells (BMSCs-Exo) reduced skin flap necrosis by increasing angiogenesis following IR injury 13 . However, the underlying mechanism remains unclear and further research is needed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(Guangzhou, China). The cultures of BMSCs as well as isolation and identification of exosomes were conducted as previously described 13 .…”
Section: Exosomes Isolation and Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the binding of surface ligands to target cells and the delivery of their internal contents, exosomes regulate a multitude of biological processes, often mirroring the functional attributes of their cells of origin. Currently, exosomes derived from mesenchymal stem cells have demonstrated therapeutic potential in several diseases [11][12][13], most notably in the context of ischaemia-reperfusion injury [14][15][16]. Intriguingly, exosomes derived from hypoxiapreconditioned BMSCs may carry altered cargos, including varied miRNAs, thus significantly enhancing their biological functionality [17][18][19].…”
Section: Introductionmentioning
confidence: 99%